Absorption of carbohydrate derived from rice in children aged 1-3 years - Agus Firmansyah; Daniel Effendi; Sri Rezeki Hadinegoro; Aswitha Boediarso; Badriul Hegar Syarif; Pramitra Gayatri (Paediatrica Indonesiana, 2001)
Many studies showsthat rice starch is well-absorbed in gastrointestinaltract, even better as a composition with electrolyte to overcome diarrhea. Although in small number, there is still a various prevalence of carbohydrate malabsorption, both with rice starch and with other starch. Khin-Maung-U found significant (66.5%) prevalence of rice starch in Burmese children malabsorption, whereas rice starch is readily obtained in countries with rice as the population staple food,so thatability to absorb rice starch in Indonesian children need to be studied. Breath hydrogen test (BHT) was performed in 86 Indonesian children aged 1-3 years on Pejaten Barat Subdistrict, Pasar Minggu, South Jakarta. Among the 86 children given meal test with rice starch cakes 80 g for eachchildren, 82 children (95.3%) can absorb rice starch well, but 4 children (4.7%) suffered from rice starch alabsorption. Currentlyit is unknown certainly the type of the malabsorption. Previous researchers found that rice malabsorption is due to enzyme deficiency and intestinal motility disturbance. In this study there were 16 children (18.6%) coming from social-economically underprivileged family, most of the mothers with junior high school and lower educational level, and the majority of parent occupation were on private and labor sectors. There was no significant relation (p >0.05) between diarrhea effects on rice starch malabsorption in 6 children (7%), history of low birth weight baby (15.1%), undernourished or malnutrition status in 35 children (40.7%), and worm and/or fungal infection in 17 children (19.8%).found that rice malabsorption is due to enzyme deficiency and intestinal motility disturbance. In this study there were 16children (18.6%) coming from social-economically underprivileged family, most of the mothers with junior high school andlower educational level, and the majority of parent occupation were on private and labor sectors. There was no significantrelation (p >0.05) between diarrhea effects on rice starch malabsorption in 6 children (7%), history of low birth weight baby(15.1%), undernourished or malnutrition status in 35 children (40.7%), and worm and/or fungal infection in 17 children(19.8%). [